IROS 2019 lifelong robotic vision: object recognition challenge [competitions] - Bae, Heechul (2024)
This report summarizes the IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2019 Lifelong Robotic Vision Competition (Lifelong Object Recognition Challenge) with the data set, rules, methods, and results from the top eight finalists (of over 150 teams) . Individual reports, data set information, rules, and released source codes can be found at the project home page.